(untitled) (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
After the recovery of democracy in Argentina, the “Trial of the Military Juntas” (1985) was depicted as a key process of the political and legal transition. Few years later, it became a subject of several struggles about its meaning and political consequences.This paper analyzes the statements about the trial made during the parliamentary debates that took place in 1986 and 1987 (usually known as the “amnesty laws” of “Punto Final” and “Obediencia Debida”). In this fra- mework, the article discusses the links established between political and legal discourse during the transitional justice process in Argentina.